Lectin typing of Campylobacter isolates. Issue 11 (November 1990) - O'Sullivan, N; Benjamin, J; Skirrow, M B
Abstract : Isolates of Campylobacter jejuni, C coli, C fetus and C laridis were tested for agglutination reactions with a panel of five lectins: Arachis hypogaea, Bauhinia purpurea, Solanum tuberosum, Triticum vulgaris and Wisteria floribunda. Twenty three patterns of agglutination (lectin types) were recorded among 376 isolates. Patterns were consistent and reproducible. Only 4.5% of isolates were untypable because of autoagglutination. Some lectin types were found exclusively or predominantly in a species, but others were shared between species. Forty two per cent of C jejuni and 35% of C coli isolates belonged to lectin type 4. There was no apparent correlation between lectin type and serotype; different lectin types were found among strains of single Penner and Lior serotypes. Lectin typing is a simple and economical procedure suitable for use in non-specialist laboratories, either as an adjunct to serogrouping or, after further development, as a sole typing scheme.